Encapsulated Escitalopram and Paroxetine Intranasal Co-Administration: In Vitro/In Vivo Evaluation - Silva, Soraia; Bicker, Joana; Fonseca, Carla; Ferreira, Nuno R.; Vitorino, Carla; Alves, Gilberto; Falcão, Amílcar; Fortuna, Ana (Frontiers in Pharmacology, 2021)
Depression is a common mental disorder. Its treatment with selective serotonin reuptake inhibitors (SSRIs) is effective only in a fraction of patients and pharmacoresistance is increasing steadily. Intranasal (IN) drug delivery to the brain stands out as a promising strategy to improve current therapeutic approaches by operating as a shuttle to overcome the blood-brain barrier. This work aimed to simultaneously administer escitalopram and paroxetine by IN route to mice. For this purpose, three nanostructured lipid carriers (NLC1, NLC2 and BorNLC) and one nanoemulsion (NE) were tested for drug loading. After their characterization, investigation of their impact on nasal cell viability and SSRIs permeability assays were performed, using a human nasal RPMI 2650 cell line in air-liquid interface. In vitro assays demonstrated that NLCs including borneol (BorNLC) significantly increased escitalopram permeability (p<0.01) and paroxetine recovery values (p<0.05) in relation to the other formulations and non-encapsulated drugs. IN and intravenous (IV) pharmacokinetic studies performed in vivo with a single dose of 2.38 mg/kg demonstrated similar results for escitalopram brain-to-plasma ratios. IN administrations delayed escitalopram peak concentrations in the brain from 15 to 60 min and no direct nose-to-brain delivery was detected. However, encapsulation with BorNLC considerably decreased escitalopram exposure in the lungs (123.55 µg.min/g) compared with free escitalopram by IN (168.50 µg.min/g) and IV (321.34 µg.min/g) routes. Surprisingly, BorNLC IN instillation increased concentration levels of paroxetine in the brain by 5-times and accelerated brain drug delivery. Once again, lung exposure was considerably lower with BorNLC (AUCt = 0.43 µg.min/g) than IV administration (AUCt = 1.01 µg.min/g) and non-encapsulated IN formulation (AUCt = 2.82 µg.min/g). Direct nose-to-brain delivery was observed for paroxetine IN administration with a direct transport percentage (DTP) of 56.91%. If encapsulated, it increases to 74.21%. These results clearly emphasize that nose-to-brain and lung exposure depend on the formulation and on the characteristics of the drug under investigation. NLCs seem to be an advantageous strategy for nose-to-brain delivery of lipophilic molecules, since they reduce systemic and lung exposure, thereby decreasing adverse effects. For hydrophilic compounds, NLCs are particularly important to decrease lung exposure after IN administration.